Patrons and Viewers in Late Antiquity - Poulsen, Birte; Birk, Stine (Book collections on Project MUSE., 2012)
"This book contains a collection of papers that focuses on the way patrons, pagan as well as Christian, conveyed messages through material and visual culture and on the reception by the viewers. The contributions investigate how patrons of luxurious buildings, elaborate grave monuments, and churches used architecture, images, and inscriptions to demonstrate political, social, and religious power. The visual arts were a strong factor in communicating identity and attitudes both in the public and private spheres also in Late Antiquity"--Page 4 of cover.